Therapeutic approach to the management of HER2-positive breast cancer metastatic to the brain. Issue 2 (28th March 2015) - Patil, Ajay; Sherbet, G.V.
Highlights This article concerns the ability of HER2 positive breast cancers to metastasise specifically to the brain. This is an important topic in cancer management and my colleague and this article provide an up-to-date account stating the current position relating to the problem and highlights new insights into tackling the problem especially in relation to patient management.